Self-concept and family environment among KOED undergraduate students in IIUM - Radin Mohd Akhmal bin Izaddin (Kuliyyah of Education, International Islamic University Malaysia, 2016)
This present research was conducted with three main objectives namely (1) to identify the level of self-concept owned by IIUM undergraduate students such as Physical moral and ethics, personal, family, social and moral traits; (2) to identify the perceptions of family environment among IIUM undergraduate students; (3) to investigate the difference between genders among IIUM undergraduate students; and (4) to examine the relationships between self-concept and family environment among IIUM undergraduate students. A total of 253 undergraduate students from three majors at the Kulliyyah of Education in IIUM participated in the survey. A 62-items questionnaire was employed to measure Tennessee Self Concept Scale (TSCS), and Family Environment Scale (FES). The items were pilot-tested before being administered to the respondents. The data were analysed quantitatively using an independent t-test and Pearson correlation coefficient. The study revealed that most of the students had high level of self-concept and positive perception of family environment. There was no statistically significant difference between male and female in their self-concept. Pearson's moment correlation showed that there was a statistically significant positive relationship between family environment and constructs of self-concept namely physical, ethics and moral, family, personal, social and personality. The result indicates a positive linear relationship between those factors. This study provides an exposure to the parents of students to ensure that they care matters relating to their children's self-development. This study may be used as a reference by future researchers to produce a better study in order to improve the self-development of students in the Kulliyah of Education, IIUM.